2016
DOI: 10.1021/acs.energyfuels.5b02872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Production Parameters on the Spray-Dried Calcium Manganite Oxygen Carriers for Chemical-Looping Combustion

Abstract: The oxygen carrier CaMn0.9Mg0.1O3−δ was successfully tested in different chemical-looping units. High methane conversion and oxygen uncoupling properties have been found for this type of material. Most of the CaMn0.9Mg0.1O3−δ oxygen carrier particles tested so far have been produced using the spray-drying method. In this work, the focus has been on studying the effects of production parameters on the properties of this important oxygen carrier. The effects of three production parameters, i.e., milling time, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Overall, these results are in good agreement with the observations of Jing et al. on CaMn 0.9 Mg 0.1 O 3− δ made by spray drying …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, these results are in good agreement with the observations of Jing et al. on CaMn 0.9 Mg 0.1 O 3− δ made by spray drying …”
Section: Resultssupporting
confidence: 93%
“…Thes pecific surface area of granules as af unction of temperature andd uration of the sintering step is shown inFigure 6. Thes pecific surface area is rather low,a se xpected from the synthesis method, and clearlyd ecreases with both sinteringt emperature and sinteringt ime.O verall,t hese results are in good agreement with the observations of Jing et al on CaMn 0.9 Mg 0.1 O 3Àd made by spray drying [39].…”
supporting
confidence: 91%
“…In both projects, different research groups contributed with their expertise to the development of calcium manganite–based materials. In the Innocuous project, this involved investigations of redox kinetics and sulfur tolerance, material screening and evaluation of spray‐drying parameters using batch testing, and continuous operation in two chemical‐looping combustors with nominal fuel inputs of 300 W and 10 kW . At a larger scale, the materials C14 (CaMn 0.9 Mg 0.1 O 3− δ ) and C28 (CaMn 0.775 Mg 0.1 Ti 0.125 O 3− δ ) were investigated in a 120 kW CLC unit .…”
Section: Introductionmentioning
confidence: 99%
“…The most important parameters affecting sintering are temperature, time and atmosphere. These parameters were investigated in depth for this system Jing et al [38] showed that temperature has the greatest effect on the quality of the final product and that after 5-6-h sintering, the effect of time is minimal. It was also shown that for upscaled calcination, an air atmosphere should be used.…”
Section: Parameters Affecting Sinteringmentioning
confidence: 99%